Distribution and Abundance of Giant Clams (Family Tridacnidae) in the South-Central Philippines - Alcala, Angel C. (Silliman Journal, 2024)
A population survey of giant clams (Family Tridacnidae) was conducted in certain coral reef areas of the Central Visayas, Western Visayas, Cagayan Islands and Palawan from February 1984 to October 1985. The largest species of Tridacna (T. gigas and T. derasa) were found to be either extinct or greatly reduced in numbers probably because of overcollection. The smaller species of Tridacna, although of. variable densities, appear to be holding their own in general. Hippopus porcellanus may also be endangered. The status of H. hippopus is uncertain, but it occurred at some reefs in the Central Visayas, Cagayan and Palawan regions.